Building Workers' Human RIghts into the Global Trading System (My University, 2016)
Document advocates for change in the world economy giving it a genuine social dimension. This includes providing basic workers' rights clause, preventing repression, discrimination, forced and child labour, and other fundamental rights which all countries regardless of their level of development can and should apply.